Transfered Tax Knowledge to Improve Taxpayer Compliance: Transfered Tax Knowledge to Improve Taxpayer Compliance - Nurcahyaning Dwi Kusumaningrum; Rachmat Hidayat; Galih Wicaksono; Yeni Puspita; Venantya Asmandani; Tree Setiawan Pamungkas; Djoko Susilo (Jurnal Mantik, 2020)
The purpose of research to know the influence of the taxpayer science level to the compliance of paying taxes by taxpayers, among others: knowledge of tax law, system knowledge and taxation functions, and the knowledge of sanctions Taxation both partially and simultaneously. Data analysis methods use SPSS software with a linear regression analysis, which is used to test the hypothesized influence of the taxpayer's level of science to pay tax compliance by both partial and simultaneous taxpayers, and See the magnitude of the coefficient. Based on the results the study concluded that in partial and simultaneous levels of taxpayer enforcement science has significant effect on the compliance of paying taxes by taxpayers.